Exclusive Breastfeeding Practices Among Postnatal Mothers: How Exclusive Are They? - Mohan P Joshi; Pushpa M Durge; Shams Khan; Samina M Ausvi (Medsci Publications, 2014)
Background - This study is designed to explore the breastfeeding practices among postnatal mothers and factors that determine exclusive breast feeding. Methods -This cross sectional study was carried out at immunization clinic at UHTC, under the tertiary care hospital in Central India during August 2012 - July 2013. The data was collected from 600 postnatal mothers using a structured proforma which was analyzed using Epi-info7.  Results -Out of 600 PNC mothers EBF was practiced in only 1.16% mothers and majority (60.90%) of them were illiterate and from upper middle (50%) socioeconomic status. Among non exclusive breastfeeding, majority of mothers had given Ghutti drops (28.8%), gripe water (21.41%), glucose water (16.86%). The period of continuation of breastfeeding had inverse association with education of mother, i.e. 70.26% illiterate mothers were continuing breastfeeding for 12 months as compared to 2.36% mothers having diploma /degree. However practice of EBF was more prevalent amongst upper middle SE class (50%) as compared to lower SE class (11.36%).There was highly significant association for initiation of breastfeeding within first hour with HE received during ANC period (p < 0.0001). The practice of EBF was 12% for under 2 month infants & merely 1% at the age of 6 months. Conclusion - Hence programmes, which support and encourage EBF practices particularly at a primary care level, focusing more on younger, well-educated women and those from lower socioeconomic class is a need of hour.